1960
DOI: 10.1139/o60-162
|View full text |Cite
|
Sign up to set email alerts
|

The Pulse Rate as a Means of Measuring Metabolic Rate in Man

Abstract: The possibility of using the pulse rate as a means of measuring metabolic rate in man has been investigated. The relation between pulse rate and metabolic rate was initially established for six subjects by a standard technique over the range of activity from lying still to moderate exertion. The reliability of the relation was tested by repetition of the measurements, and, in the range of muscular exercise, by comparing values for metabolic rate computed from the pulse rate with measured values. While a subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…Taking the high coefficients of determination into consideration, the results in this study were considered very reliable. The slope of the HR-EE curves of the subjects in the present study is clearly steeper than that of non-trained individuals previously reported by other researchers (13,14,16,20,27). It indicates that the steepness of the slope is likely to predict or estimate an individual's fitness level.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Taking the high coefficients of determination into consideration, the results in this study were considered very reliable. The slope of the HR-EE curves of the subjects in the present study is clearly steeper than that of non-trained individuals previously reported by other researchers (13,14,16,20,27). It indicates that the steepness of the slope is likely to predict or estimate an individual's fitness level.…”
Section: Discussioncontrasting
confidence: 75%
“…The HR method is relatively cheap, easy and simple, as compared to the DLW method, for monitoring EEs in various situations ( 6 , 16 -20 ). Many athletes routinely use the HR monitor as a tool for their own health management and training ( 16 ). For these reasons, we employed the HR method to estimate the TEE of athletes in this study.…”
mentioning
confidence: 99%
“…The HRM method is based on the relationship that exists between heart rate and oxygen consumption 26 . In addition to monitoring the heart rate throughout the day, two other elements are necessary to calculate TEE: the individual calibration of each person's heart rateoxygen consumption relationship, and the measurement or reliable estimate of energy expenditure under basal or sleeping conditions.…”
Section: Studies With Hrmmentioning
confidence: 99%
“…That group evaluated the utility of predicting the oxygen cost (criterion variable) of firefighting activities from indirect physiological measurements (heart rate and minute ventilation: predictive variables). Both indirect variables are independently and strongly correlated with the criterion variable (Booyens and Hervey 1960;Durnin and Edwards 1955), but can they be used interchangeably with that variable, and will they yield similar outcomes in the field? To arrive at an acceptance threshold of relevance to occupational physiologists, Notley et al (2015) invited scientists from 8 countries to define a meaningful oxygen consumption threshold for evaluating the predictive precision of those 2 variables.…”
Section: Bland-altman Plotsmentioning
confidence: 99%